Integrating Global Health Within Dental Education: Inter-University Collaboration for Scaling Up a Pilot Curriculum - Ana Lucia Seminario; Belle Chen; Jennifer Liu; Brittany Seymour (Ubiquity Press, 2020)
Background: New education programs are developing to improve global health awareness. Dental students have demonstrated interest in international settings but are largely unaware of global health topics. The Timothy A. DeRouen Center for Global Oral Health of the University of Washington (UW) and Harvard School of Dental Medicine expanded a competency-based global health curriculum (Global Health Starter Kit) by integrating it within the UW School of Dentistry (UW SOD) existing elective course "Global Oral Health" to undergraduates, pre-, and doctorate students from the UW SOD and Public Health. The study objective was to evaluate the curriculum effectiveness by assessing 1) Knowledge and Attitudes (survey), and 2) Didactic coursework (global trends, global goals, primary care, social determinants and risks, and ethics and sustainability). Methods: Eligibility included enrolled students with both pre- and post-assessments. Descriptive statistics were conducted to present demographic data. Significant changes on survey and didactic evaluations were analyzed with paired t-tests (p < 0.05). Findings: The population (N = 15) represented 88% of the class. All Knowledge categories had a significant increase (p < 0.05), except in the topic of tropical diseases. At baseline, Attitudes categories had high scores and did not significantly increase by the end of the course. Even though all Didactic categories improved, only Social Determinants and Risks showed a significant increase (p < 0.01). Conclusion: Competency-based global health learning can be implemented in the dental curriculum. While the study shows promising results, efforts to identify areas for improvement as well as considerations of the institution's culture need to be assessed and addressed for each teaching cycle.